2016
DOI: 10.1021/acsami.6b10256
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Organic Materials: Robust Polymer Films with the Outstanding Thermal Conductivity Fabricated by the Photopolymerization of Uniaxially Oriented Reactive Discogens

Abstract: For the development of advanced heat transfer organic materials (HTOMs) with excellent thermal conductivities, triphenylene-based reactive discogens, 2,3,6,7,10,11-hexakis(but-3-enyloxy)triphenylene (HABET) and 4,4',4″,4‴,4'''',4'''''-(triphenylene-2,3,6,7,10,11-hexaylhexakis(oxy))hexakis(butane-1-thiol) (THBT), were synthesized as discotic liquid crystal (DLC) monomers and cross-linkers, respectively. A temperature-composition phase diagram of HABET-THBT mixtures was first established based on their thermal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 67 publications
(108 reference statements)
0
39
0
Order By: Relevance
“…The obtained image suggests that the direction of the columns in the planar nonporous sample is apparently perpendicular to the shearing direction of the film ( Figure 9 a), which is in contrast with other examples. 35 38 Furthermore, the image shows a persistence length of the columns in the micrometer range. Calculating the Fourier transform of the image ( Figure 9 b), shows a repeating distance of 3.3 nm orthogonal to the columnar director, which corresponds to the d (100) distance of 3.23 nm as determined by X-ray diffraction.…”
Section: Resultsmentioning
confidence: 98%
“…The obtained image suggests that the direction of the columns in the planar nonporous sample is apparently perpendicular to the shearing direction of the film ( Figure 9 a), which is in contrast with other examples. 35 38 Furthermore, the image shows a persistence length of the columns in the micrometer range. Calculating the Fourier transform of the image ( Figure 9 b), shows a repeating distance of 3.3 nm orthogonal to the columnar director, which corresponds to the d (100) distance of 3.23 nm as determined by X-ray diffraction.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, increasing the thermal conductivity of the polymers themselves is essential. Kang et al 11 reported a high-thermal-conductive liquid crystalline (LC) polymer, which was photopolymerized using a thiol–ene reaction between disk-shape (discotic) liquid crystal (DLC) molecules. The thermal conductivity of the photopolymerized DLC polymer with a uniaxial orientation was estimated to be 3.0 W m –1 K –1 in the transverse direction of the oriented columnar axis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an effective development of innovative heat transfer materials for advanced devices needs a profounder understanding of the interfacial relationship between matrix and additive so that acceptable thermal conducting property can be accomplished even at small amount of filler loading [3]. Motivated by the requirement for a thermal conducting organic matrix, polymerizable liquid crystalline (LC) monomers, LC-ene and LC-thiol, were synthesized [4]. The synthesized LC network was served as a polymeric matrix for heat releasing composites packed with expanded graphite (EG) or hexagonal boron nitride (BN) [5].…”
Section: Extended Abstractmentioning
confidence: 99%